The renal patient seen by non-renal physicians: the kidney embedded in the 'milieu intérieur' - Perez-Villa, Felix; Lafage-Proust, Marie Hélène; Gielen, Eveline; Ortiz, Alberto; Spasovski, Goce; Argilés, Àngel (Oxford University Press (OUP), 2021)
Chronic kidney disease is defined as a decrease in renal function or evidence of kidney injury for >3 months. This represents an oversimplification that may confuse physicians. Thus kidney function is equated to glomerular filtration rate, which represents one of multiple kidney functions. Some potentially more important renal functions are lost earlier, such as the production for the anti-ageing factor Klotho. Overall, these changes modify the emergent properties of the body, altering the relationships between different organs and systems, in a manner that is difficult to predict the response to interventions based on normal physiology concepts, as there is a novel steady state of interorgan relations. In this regard we now discuss the impact of CKD on heart failure; osteomuscular and joint pain and bone fragility and fractures; and osteosarcopaenia as seen by a cardiologist, a rheumatologist and a geriatrician.